Assessment of cardiovascular risk in Tunisia: applying the Framingham risk score to national survey data. Issue 11 (30th November 2016) - Saidi, O; Malouche, D; O'Flaherty, M; Ben Mansour, N; A Skhiri, H; Ben Romdhane, H; Bezdah, L
Abstract : Objective: This paper aims to assess the socioeconomic determinants of a high 10 year cardiovascular risk in Tunisia. Setting: We used a national population based cross sectional survey conducted in 2005 in Tunisia comprising 7780 subjects. We applied the non-laboratory version of the Framingham equation to estimate the 10 year cardiovascular risk. Participants: 8007 participants, aged 35–74 years, were included in the sample but effective exclusion of individuals with cardiovascular diseases and cancer resulted in 7780 subjects (3326 men and 4454 women) included in the analysis. Results: Mean age was 48.7 years. Women accounted for 50.5% of participants. According to the Framingham equation, 18.1% (17.25–18.9%) of the study population had a high risk (≥20% within 10 years). The gender difference was striking and statistically significant: 27.2% (25.7–28.7%) of men had a high risk, threefold higher than women (9.7%; 8.8–10.5%). A higher 10 year global cardiovascular risk was associated with social disadvantage in men and women; thus illiterate and divorced individuals, and adults without a professional activity had a significantly higher risk of developing a cardiovascular event in 10 years. Illiterate men were at higher risk than those with secondary and higher education (OR=7.01; 5.49 to 9.14). The risk in illiterate women was more elevated (OR=13.57; 7.58 to 24.31). Those living in an urban area had a higher risk (OR=1.45 (1.19 to 1.76) in men and OR=1.71 (1.35 to 2.18) in women). Conclusions: The 10 year global cardiovascular risk in the Tunisian population is already substantially high, affecting almost a third of men and 1 in 10 women, and concentrated in those more socially disadvantaged.